Prognostic value of patient-reported outcomes from international randomised clinical trials on cancer: a systematic review. Issue 12 (December 2019) - Mierzynska, Justyna; Piccinin, Claire; Pe, Madeline; Martinelli, Francesca; Gotay, Carolyn; Coens, Corneel; Mauer, Murielle; Eggermont, Alexander; Groenvold, Mogens; Bjordal, Kristin; Reijneveld, Jaap; Velikova, Galina; et al.
Summary: A previous review published in 2008 highlighted the prognostic significance of baseline patient-reported outcomes (PROs) as independent predictors of the overall survival of patients with cancer in clinical studies. In response to the methodological limitations of studies included in the previous review, recommendations were subsequently published in the same year to promote a higher level of methodological rigour in studies of prognostic factors. Our systematic review aimed to provide an update on progress with the implementation of these recommendations and to assess whether the methodological quality of prognostic factor analyses has changed over time. Of the 44 studies published between 2006 and 2018 that were included in our review, more standardisation and rigour of the methods used for prognostic factor analysis was found compared with the previous review. 41 (93%) of the trials reported at least one PRO domain as independently prognostic. The most common significant prognostic factors reported were physical functioning (17 [39%] studies) and global health or quality of life (15 [34%] studies). These findings highlight the value of PROs as prognostic or stratification factors in research across most types of cancer.